Pengaruh Lifestyle, Islamic Branding, dan Social Media Marketing terhadap Minat Beli Hijab Pashmina Kaos : (Studi Mahasiswa Universitas Trunojoyo Madura) - Nur Ayniyah Afifah; Luluk Hanifah (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2025)
The halal industry, particularly halal fashion, has become a global trend, including in Indonesia, which has the largest Muslim population. This study aims to analyze the impact of Lifestyle, Islamic Branding, and Social Media Marketing on the purchase interest of pashmina hijabs among students at the University of Trunojoyo Madura. The method used is descriptive quantitative with data collection through online questionnaires to 100 students. The results show that Lifestyle has a significant positive impact on purchase interest (coefficient 0.444), while Islamic Branding has a positive but not significant impact (coefficient 0.039). Social Media Marketing also has a positive and significant impact on purchase interest (coefficient 0.367). Simultaneously, the three variables significantly influence, with a contribution of 33,1%. These findings suggest that improving Lifestyle and Social Media Marketing can enhance purchase interest, while Islamic Branding does not have a significant impact.